Decoding consumer perspective for tech-based health insurance products - Anushka Goel; Nupur Soti; Udita Taneja; Ashish Kumar (Innovation & Management Review, 2025)
Technology-driven health insurance products have significant applications for business firms and customers. With their growing popularity, these products can disrupt legacy insurance systems. Based on this notion, this study seeks to identify and validate the factors that affect customers' attitudes toward their buying intentions and readiness to pay for these products.This study extended the technology acceptance model with privacy, trust, purchase intention and willingness to pay to improve its predictive capability. The data were analyzed using the partial least square technique on a sample comprising 150 respondents.The results indicated that all model variables except for privacy concerns were significant and influenced consumers' attitudes toward these technology-driven products. The authors also found a significant difference in the influence of trust on attitude when comparing the genders. A significant mediation between perceived ease of use and attitude was also established.The empirical investigation in this study offers valuable insights for insurance companies to plan effective marketing strategies that help them disseminate information about the utility and user-friendly aspects of their products, thereby increasing positive attitudes and the plausibility of adoption. It is also advised that the companies tie up with reliable technology platforms. Pricing policies can be designed keeping in mind that the consumers are willing to pay even more to avail the benefits of the products.The current study intends to fill the gaps in the existing literature by demystifying the purchase intention-willingness to pay relation regarding technology-based health insurance products in India.
https://www.emerald.com/inmr/article-supplement/1278334/docx/inmr-10-2023-0191_suppl1/
Keywords: 650; Technology-based health insurance; Wearable technology; Willingness to pay; Purchase intention; Extended TAM